Design of Indole-Functionalized Phosphepines towards New Organic Chromophores - Liu, Zhaoxin; Ren, Yi (Synlett, 2024)
Organic chromophores emerged as diverse functional materials in the areas of organic catalysis, toxic materials sensing, bio-imaging, and organic electronic devices. With rich chemical and electronic structures, main-group elements have been extensively implanted in organic chromophores to fine-tune the chemical/electronic structures and optoelectronic properties. In this Synpact article, we present a concise overview of the development of phosphorus (P)-containing organic chromophores, further highlighting our recent contributions in the field. A new aspect of combining the P element with the indole moiety was pursued to construct a new series of seven-membered P-organic chromophores; namely, indole-functionalized phosphepines. The new combination endowed the system with rich chemical and electronic structures, for which intriguing photophysical properties were consequently revealed. The combination provided an efficient synthetic protocol to access new P-heterocycles and also offered a new strategy to design functional organic chromophores.
Keywords: heterocycles; phosphepines; organic chromophores; conformation; photophysical property